Pengembangan Aplikasi Pengaduan Masyarakat DP3A Kabupaten Nabire Berbasis Web menggunakan Metode Agile - Kornelia Kidi Olarne; Arief Rahman Hakim (Jurnal Teknologi dan Informatika, 2025)
The Department of Women's Empowerment and Child Protection (DP3A) of Nabire Regency is responsible for implementing government tasks related to women's empowerment and child protection. However, the existing complaint handling process is still manual, leading to inefficiencies. This research aims to develop a web-based public complaint system using the Agile method to improve service quality. The development process follows Agile principles, emphasizing iterative development and stakeholder collaboration. The resulting system allows the public to submit complaints online, track their status, and receive timely responses. The implementation of this system is expected to enhance transparency, accountability, and responsiveness in handling public complaints.